Analisis Faktor Pemilihan Moda Transportasi Umum Konvensional dan Transportasi Umum Online di Kabupaten Nganjuk - Sadewa, Ferderiko Khova; Hartatik, Nurani; Rizkiardi, Aditya (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
One important aspect of transportation is mode choice. This mode selection is an important step in transportation planning and plays a key role in determining transportation policy, especially related to the type of mode and infrastructure available. This study aims to analyze the factors that influence the selection of online and conventional public transportation modes by people in Nganjuk Regency, using questionnaires distributed to people in Nganjuk Regency and data processing using the help of the SPSS application. This study also measures how much influence the variables of tariff, ease of obtaining transportation modes, service quality, availability of transportation modes, and travel time have on the selection of transportation modes in Nganjuk Regency. From the results of data processing obtained through questionnaires that have been distributed to 400 respondents in Nganjuk Regency, obtained, namely tariffs, ease of obtaining transportation modes, service quality, availability of transportation modes, and travel time. Then for the magnitude of the influence of these variables on the selection of online public transportation modes by 50% and conventional public transportation modes is 82%.